2017
DOI: 10.1111/1475-6773.12752
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Population Average Treatment Effects in the FIRST Trial: Application of a Propensity Score‐Based Stratification Approach

Abstract: Propensity score-based poststratification can be valuable tools to address trial generalizability but may yield imprecise estimates of PATE when sparse strata exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Fourth, our interview data were obtained only from sites participating in the FIRST trial. Previous work has shown that these sites do not differ substantially from nonparticipating residencies; thus, we expect our findings to be representative of all general surgery residencies . Finally, our analysis of preparation is limited to those factors measured in the ABSITE survey.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fourth, our interview data were obtained only from sites participating in the FIRST trial. Previous work has shown that these sites do not differ substantially from nonparticipating residencies; thus, we expect our findings to be representative of all general surgery residencies . Finally, our analysis of preparation is limited to those factors measured in the ABSITE survey.…”
Section: Discussionmentioning
confidence: 96%
“…Previous work has shown that these sites do not differ substantially from nonparticipating residencies; thus, we expect our findings to be representative of all general surgery residencies. 33 Finally, our analysis of preparation is limited to those factors measured in the ABSITE survey. We acknowledge that other unmeasured factors such as experience before medical school, mentorship, and other preparatory courses may also influence preparation for residency.…”
Section: Limitationsmentioning
confidence: 99%
“…Using a PSM approach, Lai et al [ 10 ] compared the results of patients treated with SXC monotherapy from both real world and RCT cohorts and found that SXC monotherapy is at least as effective in real-world settings as within the RCT. Similarly, Chung et al [ 11 ] used propensity score-based poststratification to generalize the results of the Flexibility in Duty Hour Requirements for Surgical Trainees Trial to the nonrepresentative samples. In addition, Godley et al [ 12 ] used propensity score based methods to assess the impact of dosage levels of Volunteer Recovery Support for Adolescents across measures such as frequency of substance used and emotional problems.…”
Section: Use Of Propensity Score Matching In Randomized Controlled Tr...mentioning
confidence: 99%